1978
DOI: 10.1017/s0079497x00010161
|View full text |Cite
|
Sign up to set email alerts
|

The Excavation of an Iron Age Souterrain and Settlement at Carn Euny, Sancreed, Cornwall

Abstract: The ancient village of Carn Euny, formerly known as Chapel Euny, lies on a south-west slope just above the 500 foot contour in the parish of Sancreed in West Cornwall (fig. 1). The granite uplands of the region are rich in antiquities, as a glance at a recent survey shows (Russell 1971), not least those of the prehistoric period. The hill on which the site is situated is crowned by the circular Iron Age Fort of Caer Brane (pl. 27). Across the dry valley to the north-west rises the mass of Bartinny Down, with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Analysis has suggested butter reaches its 'bog constituency' within a couple of years (Cronin et al 2007). In the UK, the Iron Age marks a considerable period of underground experimentation with cold storage: the fogoues of Cornwall and the souterrains of Ireland and Scotland, for example (Christie et al 1978;Armit 5.4 The Rosberry keg and bog butter, dating to 360-200 BC. All rights reserved and permission to use the figure must be obtained from the copyright holder.…”
Section: Bog Bodies 130 130mentioning
confidence: 99%
“…Analysis has suggested butter reaches its 'bog constituency' within a couple of years (Cronin et al 2007). In the UK, the Iron Age marks a considerable period of underground experimentation with cold storage: the fogoues of Cornwall and the souterrains of Ireland and Scotland, for example (Christie et al 1978;Armit 5.4 The Rosberry keg and bog butter, dating to 360-200 BC. All rights reserved and permission to use the figure must be obtained from the copyright holder.…”
Section: Bog Bodies 130 130mentioning
confidence: 99%
“…Within the middle of the enclosure are three ring-cairns, including a large central example, which may have formed the focal point for the monument. As at Bartinney and Godolphin, the enclosure is situated above the prehistoric field systems and occupation areas, and it is located to the east of the Iron Age settlement of Carn Euny, which lies on the slope below it (Christie 1978). Weatherhill (1985, 39-40) suggested that the site was an unfinished Iron Age hillfort.…”
Section: Misidentified Monuments?mentioning
confidence: 99%
“…2,11,12); and 150 m south of the nucleated settlement a ruinous fogou (souterrain) sits within an uninterpretable earthwork complex (Fig. 2, 13), which may be the remains of a courtyard house or an earlier settlement; Cornish fogous have been dated to the Iron Age (Christie 1978;Quinnell 1986, 119). If these are indeed all courtyard houses, are the nucleated and dispersed houses contemporaneous, or was there a major change in the pattern of settlement?…”
Section: The 'Perpetuated' Fieldsmentioning
confidence: 99%